Effect of Telephone Counseling during Post-Partum Period on Women\'s Quality of Life - Z Khakbazan; Sh Golyan Tehrani; R Payghambardoost; A Kazemnejad (Tehran University of Medical Sciences, 2010)
Background & Aim: Pregnancy and post-partum period are accompanied by important changes in women;aposs quality of life. Patient counseling is an effective way to improve quality of life. This study aimed to assess the effect of telephone counseling on the quality of life among women with a normal vaginal delivery in Razi hospital in Marand.Methods & Materials: In this randomized clinical trial, 260 women were recruited to the study. The participants who had met the inclusion criteria were randomly allocated in two intervention and control groups. The intervention group (n=130) received telephone counseling twice at the first week for 20 minutes and then once a week from the 2nd week to the 6th week. Moreover, we had provided a 24-hour hotline for women. The control group (n=130) received the routine care. Data were gathered using a demographic sheet, a postpartum problem;aposs checklist, and the SF-36 quality of life questionnaire. Data were analyzed using SPSS-13.Results: The results showed no significant differences in physical and mental quality of life in the first day of post-partum between two groups. The women;aposs quality of life in both physical and mental dimension were significantly higher in the intervention group in the 42nd day after childbirth (P<0.001).Conclusion: Telephone counseling by midwives could help to improve women;aposs quality of life in post-partum period. More studies are recommended.